Integrated Bacteria-Fungi Diversity Analysis Reveals the Gut Microbial Changes in Buffalo With Mastitis - Chen, Xiushuang; An, Miao; Zhang, Wenqian; Li, Kun; Kulyar, Muhammad Fakhar-e-Alam; Duan, Kun; Zhou, Hui; Wu, Yu; Wan, Xin; Li, Jianlong; Quan, Lingtong; Mai, Zhanhai; et al. (Frontiers in Veterinary Science, 2022)
Gut microbial community is closely related to mastitis, but studies regarding the influences of mastitis on gut microbiota in buffalo remains scarce. Herein, we characterized the differences of gut bacterial and fungal communities between mastitis-affected and healthy buffalo. Interestingly, although mastitis had no effect on gut bacterial and fungal diversities in the buffalo, some bacterial and fungal taxa were significantly altered. Bacterial and fungal taxonomic analysis showed that the preponderant bacterial phyla (Firmicutes and Bacteroidetes) and fungal phyla (Ascomycota and Basidiomycota) in buffalo were the same regardless of health status. At the level of genus, the changes of some gut bacterial and fungal abundances between both groups were gradually observed. Compared with healthy buffalo, the proportions of 3 bacterial genera (uncultured_bacterium_f_Muribaculaceae, Eubacterium_nodatum_group and Lachnoclostridium_10) and 1 fungal genera (Pichia) in the mastitis-affected buffalo were significantly increased, whereas 4 bacterial genera (Ruminococcus_2, Candidatus_Stoquefichus, Turicibacter and Cellulosilyticum) and 4 fungal genera (Cladosporium, Thermothelomyces, Ganoderma and Aspergillus) were dramatically decreased. Taken together, this research reveals that there are significant differences in the compositions of gut microbial community between the healthy and mastitis-affected buffalo. To our knowledge, this is the first insight into the charac teristics of the gut microbiota in buffalo with mastitis, which is beneficial to understand the gut microbial information of buffalo in different health states and elucidate the pathogenesis of buffalo mastitis from the gut microbial perspective.